The effect of the sowing date and the fertility on the yield and their components of three small grain species in the region of the plains with petrocalcic subsoil layer of La Pampa province (Semiárida, 2020)
The objective of this work was to analyze the effect of the sowing date and the fertility on the grain yield and their components of three small grain species in the region of the plains with petrocalcic subsoil layer of La Pampa. With this purpose were used: durum wheat (Triticum durum Desf.), bread wheat (T. aestivum L.) and triticale (X Triticosecale Wittmack) during three growing seasons, in two sowing dates (principle of July and principle of August) and under two fertility conditions (control and nitrogen-phosphorous fertilizers). The first sowing dates always showed greater yield that the second. The reduction of the grain yield was given in its main part by a decrease in the number of grains for spike and in smaller measure of the weight grains. This diminution in the mentioned components showed in a smaller harvest index. The greatest variation in the grain yield was due to the effect of the growing season and its water availability, nevertheless that the sowing date and the genotype influenced significantly. The triticale was more stable before low water availability e conditions than durum and bread wheat. The fertilization showed an unequal behaviour, with one year in that the grain yield increased, another in that it didn't modify it and another in which produced a decrease in the same one. Lastly, the grain yield of small grains you can increase with handling tools that don't imply a great modification in the cost of production of a crop, as the election of the genotype and the sowing date.
Keywords: small grains; sowing date; fertility; growing seasons